Penanaman Karakter Gemar Membaca Melalui Program LIterasi Sekolah Rakica di SD Negeri Taman Ciruas Permai - Syamsuri, Chusnul Khotimah; M. Hosnan; Jamaludin, Ujang (Universitas Nusantara PGRI Kediri, 2020)
This study aims to determine the process of cultivation of delight in reading character by rakica school literacy program reading along with supporting and inhibiting factors through the rakica school literacy program at Taman Ciruas Permai public elementary school program. This research is a descriptive qualitative research. Data collection techniques used are interview, observation and documentation. Then analyzed using the Miles and Huberman model. The results of the study are as follows: (1)The process of cultivation of delight in reading character by rakica school literacy program is carried out based on the literacy stage, which is the habituation, development and learning phase. active in the implementation of the rakica program by providing guidance to students, then from outside the school such as student guardians by helping schools provide the facilities needed by students, as well as the local government by providing books to the school.